Judo, one of the safest olympic sports: injury statistics from Europe's top level judo competitions - Smolders, P. (The Arts and Sciences of Judo, 2021)
The main goal of the study was to gather statistical data on injuries occurring during Europe`s top-level judo competitions. We aim to obtain epidemiological data concerning frequency of injuries, anatomical localisation, type of injury, seriousness of injury and possible differences between weight categories. During the period 2005 to 2019, at Europe`s top tournaments (European Open, European Championships), a member of the EJU Medical Commission present, together with the local physician in charge, filled in the EJU Injury Registration form. This form registers sex and weight category of the judoka, anatomical localisation, type of injury, tissue involved, site of the lesion and whether the judoka can continue the fight or must be transported to hospital. During 123 top level competitions, with a total of 25,397 competitors, 664 injuries were registered (2.6% of all competitors needed medical assistance). By anatomical location, the knee (18.5%), shoulder (15.6%) and elbow (15.2%) were sites for the most common injuries. Distention (43.6%) was by far the most frequent injury type, followed by contusion (22.6%). There is no significant statistical difference in injury incidence between men and women, although women have significantly more elbow injuries (p<0.01). When weight categories are compared, heavy weights have a remarkably low number of elbow injuries, with more knee injuries being observed. Lighter weights seem to be more prone to elbow injuries. During the registration period, an injury incidence of only 2.6% was registered. Ongoing statistical monitoring can help with the prevention of judo injuries.